(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the interpretation of love in the works of Alisher Navoiy and William Shakespeare. It analyzes how both authors portray love through their literary forms, imagery, and philosophical perspectives. The study highlights similarities and differences in their artistic approaches and reveals the universal nature of love as a central theme in world literature.